Heart Rate Data Collector for Covid-19 Patient using IoT and LoRa Network - Adri, Nurul Azizah; Hassan, Arshad; Alias, Hannan; Ismail, Faizal (Multidisciplinary Applied Research and Innovation, 2023)
Patients with covid 19 symptoms were previously monitored by the doctor or nurses. Patients’ data were collected directly. Because of the virus can spread from one individual to another, health staff need to wear full personal protective equipment (PPE) to gather patient health data. They had to move from one patient to the next to gather information.The main objective of this project is to collect the heart rate data wirelessly using LoRa and IoT by using MAX30100 sensor to intergrate the pulse oximetry and heart rate monitoring. The presented work is to reduce the use of medical workers and provide online access for medical personnel. This low cost device will help the medical assistant to record patients’ data effectively.